The Effect of the STEAM Method on Children’s Creativity - M.A Muazar Habibi (Postgraduate, University of Mataram, 2023)
In the globalization era, education requires schools to create students who can think critically in terms of STEAM (Science, Technology, Engineering, Art, and Mathematics) and carry out their activities independently. For instance, the rapid development of technology has changed how people communicate, interact, eat, and perform other things. This causes education to become important in preparing students to be independent. Therefore, teachers need to follow the latest developments regarding strategies, approaches, or methods in the learning process. Agyei, D. D., & Voogt, J. (2012). Education is an effort used in helping students to develop their potential, abilities, and talents. This study aims to examine the effect of STEAM (Science, Technology, Engineering, Art, and Math) on the creativity of children aged 5-6 years at Lenterahati Islamic boarding school. In this study, the STEAM method is the independent (X) and creativity is the dependent variable (Y). This instrument preparation is known as the Torrance test of creative thinking consisting of fluency, flexibility, originality, and elaboration skills. A total of 25 children in the preschool were selected as the participants using a pretest and posttest. The results showed there is a difference in students' creativity before and after receiving STEAM treatment. This method uses loose parts which help to increase children's creative thinking. High creativity is characterized by fluent, flexible, original, and detailed skills. Therefore, the use of STEAM in learning can increase children's creativity and provide them the ability to solve problems as well as connect with the environment.